Cost effectiveness of perindopril in reducing cardiovascular events in patients with stable coronary artery disease using data from the EUROPA study. Issue 9 (29th November 2006) - Briggs, Andrew; Mihaylova, Borislava; Sculpher, Mark; Hall, Alistair; Wolstenholme, Jane; Simoons, Maarten; Deckers, Jaap; Ferrari, Roberto; Remme, Willem J; Bertrand, Michel; Fox, Kim
Abstract : Background: The EUropean trial on Reduction Of cardiac events with Perindopril in stable coronary Artery disease (EUROPA) trial has recently reported. Objective: To assess the cost effectiveness of perindopril in stable coronary heart disease in the UK. Methods: Clinical and resource use data were taken from the EUROPA trial. Costs included drugs and hospitalisations. Health-related quality of life values were taken from published sources. A cost-effectiveness analysis is presented as a function of the risk of a primary event (non-fatal myocardial infarction, cardiac arrest or cardiovascular death) in order to identify people for whom treatment offers greatest value for money. Results: The median incremental cost of perindopril for each quality-adjusted life year (QALY) gained across the heterogeneous population of EUROPA was estimated as £9700 (interquartile range £6400–£14 200). Overall, 88% of the EUROPA population had an estimated cost per QALY below £20 000 and 97% below £30 000. For a threshold value of cost effectiveness of £30 000 per QALY gained, treatment of people representing the 25th, 50th (median) and 75th centiles of the cost effectiveness distribution for perindopril has a probability of 0.999, 0.99 and 0.93 of being cost effective, respectively. Cost effectiveness was strongly related to higher risk of a primary event under standard care. Conclusions: Whether the use of perindopril can be considered cost effective depends on the threshold value of cost effectiveness of healthcare systems. For the large majority of patients included in EUROPA, the incremental cost per QALY gained was lower than the apparent threshold used by the National Institute for Health and Clinical Excellence in the UK.